A General Method to Grow Porous α‐Fe2O3 Nanosheets on Substrates as Integrated Electrodes for Lithium‐Ion Batteries. Issue 5 (28th March 2014) - Li, Linlin; Wu, Hao Bin; Yu, Le; Madhavi, Srinivasan; Lou, Xiong Wen (David)
<x xml:space="preserve">Abstract</x> Porous α‐Fe2O3 nanosheets grown on various metallic substrates are successfully fabricated through a facile solvothermal method combined with a thermal treatment. As an advanced integrated electrode for lithium‐ion batteries, the architecture exhibits enhanced cycling stability and excellent rate capability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>